1178 The difference in external radiation exposure depending on the working process among radiation decontamination workers in fukushima. (24th April 2018) - Kakamu, Takeyasu; Hidaka, Tomoo; Kumagai, Tomohiro; Masuishi, Yusuke; Endo, Shota; Sato, Sei; Fukushima, Tetsuhito
Abstract : Introduction: Since the occurrence of the Fukushima Daiichi Nuclear Power Plant Accident, radiation decontamination work has been conducted in Fukushima. In this work, several different working processes are typically performed simultaneously in a single area. However, the difference in external radiation dose rates between processes is unknown. The aim of this study was to compare external radiation exposure of decontamination workers between processes. Methods: The subjects were 130 radiation decontamination workers who worked at the same site from April to December 2016. We obtained the external radiation dose rates from a radiation decontamination company, whose workers wear external radiation dose monitors at all times when working. The monitors are used to calculate the external radiation dose rates every month. We used the data from April to December 2016. We divided the workers into 5 groups according to their working processes; administration, removal, collection, and transportation of contaminated soil, and filling of uncontaminated soil. We compared the total radiation dose per month and total overall dose during the period between the groups. Result: The median (25–75 percentile) external radiation dose rate during the period was 0.82 (0.72–0.91) mSv. The process with the highest exposure was removal of contaminated surface soil, with a median of 0.96 (0.91–0.99) mSv. The exposure rates of administration and filling of uncontaminated soil were 0.64 (0.57–0.71) and 0.71 (0.65–0.77) respectively, which were lower than those in the other processes. Discussion: The cumulative radiation exposure rates in a single area differed according to working process. Although the differences in radiation exposure were relatively small, cumulative exposure may increase in the long term. This radiation decontamination work is globally unprecedented and the effect of low-dose radiation exposure is unknown. Continuous monitoring of low-dose radiation, as well as surveying its effects, are necessary.